The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (University of Minnesota Press, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

De la guerrière à la citoyenne. Porter les armes pendant l'Ancien Régime et la Révolution française - Godineau, Dominique (Clio. Femmes, Genre, Histoire, 2004)
Alors que la guerre était associée au masculin, quelques femmes en France ont combattu au cours des guerres civiles des XVIe-XVIIe siècles ou ont servi dans les armées royales, qu'accompagnaient de plus de nombreuses civiles. Avec la Révolution française, le service dans la garde nationale et, moins directement, dans l'armée est lié à la citoyenneté. En réclamant le port des armes au sein de la garde nationale, des militantes révolutionnaires revendiquaient ainsi un des droits politiques du citoyen, ce qui provoqua un ferme refus. Mues par le désir de défendre la République et de partager avec les hommes la gloire de se battre pour elle, des citoyennes s'engagèrent par ailleurs individuellement dans les armées, où elles continuèrent à servir après le décret du 30 avril 1793 qui les en chassait. Les demandes d'armement des militantes et les réponses qui leur sont apportées, ainsi que les histoires, les propos des soldâtes et les réactions qu'elles ont suscitées permettent d'analyser l'association entre masculin, armes et citoyenneté et d'étudier les mécanismes de l'exclusion des femmes des armées.
Keywords: 1500-1599; 1600-1699; 1700-1799; ancien régime; approches et analyses; cours; discipline; guerre; his4330; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; rapports sociaux de sexe; révolution française; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Public/Privé - Lamoureux, Diane (Dictionnaire critique du féminisme, 2004)
Keywords: approches et analyses; cours; discours dominant; fem1000; histoire et politique; maternité; mouvements féministes; outils; ouvrages de références; patriarcat; premier cycle; systèmes d'oppressions; thématiques

« Des femmes et de la territorialité » Début d’un dialogue sur la nature sexuée des droits des autochtones - Woudenberg, Gerdine Van; Lapierre, Christine (Recherches amérindiennes au Québec, 2004)
Cet article, qui se situe dans l’ensemble des discours sur les droits des autochtones, explore de façon spécifique le sujet du rapport des femmes à la territorialité. En utilisant comme étude de cas les cultures wabanakies de la côte Est, l’auteure réexamine de manière critique les documents historiques pour analyser le rapport des femmes au « lieu » à travers leur relation à leur environnement et elle étudie comment le contexte de cette relation a été transformé par les processus de colonisation. Puisque ce texte s’insère dans le large champ des discours sur les droits autochtones, il soulève des questions importantes sur la position des femmes autochtones dans les processus actuels de reconnaissance des droits et des titres, non seulement comme participantes actuelles mais aussi comme acteurs historiques.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; environnement; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; territoire; thématiques; wabanakie

Creating a critical faith-centered space for antiracist feminism: Reflections of a muslim scholar-activist - Zine, Jasmin (Journal of Feminist Studies in Religion, 2004)
Keywords: antiracisme; approches et analyses; cours; discipline; fem3400; féminisme décolonial; histoire et politique; premier cycle; racisme; ressource en ligne; science des religions; sciences humaines; système colonial; systèmes d'oppressions; thématiques